A importância da língua de sinais para o processo de ensino e de aprendizagem da língua portuguesa como segunda língua para surdos. - Araújo, Daniela Lopes de (Universidade Federal do Tocantins, 2022)
Talking about inclusive education is a necessity, it is true that much has been said about the subject, but it is still little. Inclusion has been a subject much debated by many scholars, all this debate has arisen as a result of the search for the rights of people with disabilities. Talking about the deaf and their rights leads us first to clarify the fact that is often unknown or misunderstood by society, which is to make it clear that the deaf person is not considered a disabled person, given that he has all his cognitive preserved, so he has in perfect condition your mental abilities. This debate has generated many consequences and consequences. As an objective, we will discuss a little of the history of the deaf over time, highlighting some historical concepts about the inclusion process. Briefly, we will also address the concept of deafness and highlight some public policies and the challenge of including. Dealing with this theme also leads us to analyze some Methodologies used in Education for the Deaf. The importance of sign language for the process of teaching and learning Portuguese as a second language for the deaf. Another methodology used in the education of the deaf is Bilingualism, we intend to talk a little about this factor. Through this work, we intend to promote a reflection on the process of inclusion of the deaf and, more than that, to promote awareness in society and in each reader, since each citizen has his share of contribution in this process.